2016
DOI: 10.1542/peds.2015-3500
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Rehabilitation for Medicaid-Insured Children Hospitalized With Traumatic Brain Injury

Abstract: OBJECTIVES To describe the prevalence of postdischarge outpatient rehabilitation among Medicaid-insured children hospitalized with a traumatic brain injury (TBI) and to identify factors associated with receipt of services. METHODS Retrospective cohort of children <21 years, hospitalized for a TBI between 2007 and 2012, from a national Medicaid claims database. Outcome measures were receipt of outpatient rehabilitation (physical, occupational, or speech therapies or physician visits to a rehabilitation provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…13 In brief, it contains individual-level inpatient and outpatient medical claims; each claim includes date, place, and type of medical service and associated diagnoses. It also provides demographic information on the patient at the time of service, and data on Medicaid enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…13 In brief, it contains individual-level inpatient and outpatient medical claims; each claim includes date, place, and type of medical service and associated diagnoses. It also provides demographic information on the patient at the time of service, and data on Medicaid enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…3,11,71 In a recent study of Medicaid-insured children hospitalized after TBI, only 29% received any type of outpatient services regardless of TBI severity. 72 Furthermore, a study of Medicaid service availability in the state of Washington found that less than 20% of all rehabilitation providers in the statewide database accepted Medicaid. 73 …”
Section: Practices Of Carementioning
confidence: 99%
“…Many parents leave the hospital with limited understanding of a need to change their child’s school program as a result of a TBI 10 and experience difficulties coordinating healthcare and school-based rehabilitation services. 72 School personnel often do not have training on identification and management of students with TBI. 76,77 …”
Section: Practices Of Carementioning
confidence: 99%
See 2 more Smart Citations